The Effect Of Genre-Based Approach On Students’ Writing Ability In Recount Text At Grade X Of SMA Negeri 7 Medan - Novia Klopaking Br Sinaga; Nurhayati Sitorus; Harpen H. P. Silitonga (Jurnal Kajian Ilmu Pendidikan (JKIP), 2026)
This study aimed to examine the effect of the Genre-Based Approach on students’ writing ability in recount text at Grade X of SMA Negeri 7 Medan. The study employed a quasi-experimental research design using a one-group pre-test and post-test model. The participants of the study consisted of 30 students selected from one class of Grade X. The data were collected through a writing test in which the students were instructed to compose a recount text. The collected data were analyzed using descriptive statistics and a paired sample t-test. The findings indicated that the mean score of the pre-test was 67.7, while the mean score of the post-test increased to 81.57 after the implementation of the Genre-Based Approach. The result of the hypothesis testing showed that the value of  (13.66) was higher than the value of  (2.045) at the level of significance of 0.05 with 29 degrees of freedom. This result indicates that the null hypothesis was rejected and the alternative hypothesis was accepted. Based on the findings of the study, it can be concluded that the Genre-Based Approach had a significant effect on students’ writing ability in recount text.